ANALYSIS OF THE APPLICATION OF WORK DISCIPLINE AND WORK MOTIVATION IN IMPROVING THE PERFORMANCE OF NON ASN EMPLOYEES IN THE CLEANING SECTION AT THE CENTER FOR STATE CIVIL STAFF DEVELOPMENT IN BOGOR - Sunarto, Ading; Latif, Latif (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This research is entitled "Analysis of the Application of Work Discipline and Work Motivation in Improving the Performance of Non-ASN Employees in the Cleaning Department at the Center for Civil Service Personnel Development in Bogor. This research aims to analyze the application of work discipline and work motivation in improving employee performance. The research method used is qualitative research with a non-probability sampling technique, namely purposive sampling. The data collection procedures for this research are observation, interviews, documentation, triangulation. The data analysis techniques in this research are data reduction, data presentation, drawing conclusions and verification, Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis and Quantitative Strategic Planning Matrix (QSPM) analysis. The results of this research show that the implementation of employee work discipline is quite good, because there are some employees who obey the regulations set by the agency. Apart from that, the implementation of employee work motivation is good because there are awards given by agency leaders. By implementing work discipline and work motivation, employee performance can be improved. And employee performance is good because the resulting performance has a good impact on the individual and the agency. The results of the SWOT analysis show that it is in quadrant I, namely aggressive, where the values ​​of the available to take advantage of opportunities. And also the results of the QSPM analysis are that there are 5 priority alternative strategies that can be used as strategies to improve employee performance, including improving good service, employee attitudes and employee responsibility at 6.50, controlling work so that it runs professionally at 6.42, maintaining relationships. Good cooperation between employees and other agencies amounted to 6.13, increased potential employee abilities by 5.91, increased assertiveness and concern by 5.22